Overexpression of HvAKT1 improves drought tolerance in barley by regulating root ion homeostasis and ROS and NO signaling. (7th August 2020) - Feng, Xue; Liu, Wenxing; Cao, Fangbin; Wang, Yizhou; Zhang, Guoping; Chen, Zhong-Hua; Wu, Feibo
Abstract : AKT1 originated from streptophyte algae, and HvAKT1 improves drought tolerance in barley via enhancing root K + uptake and exerting pleiotropic effects on root H + -ATPase, and H2 O2 and NO signal molecules. Abstract: Potassium (K + ) is the major cationic inorganic nutrient utilized for osmotic regulation, cell growth, and enzyme activation in plants. Inwardly rectifying K + channel 1 (AKT1) is the primary channel for root K + uptake in plants, but the function of HvAKT1 in barley plants under drought stress has not been fully elucidated. In this study, we conducted evolutionary bioinformatics, biotechnological, electrophysiological, and biochemical assays to explore molecular mechanisms of HvAKT1 in response to drought in barley. The expression of HvAKT1 was significantly up-regulated by drought stress in the roots of XZ5—a drought-tolerant wild barley genotype. We isolated and functionally characterized the plasma membrane-localized HvAKT1 using Agrobacterium -mediated plant transformation and Barley stripe mosaic virus -induced gene silencing of HvAKT1 in barley. Evolutionary bioinformatics indicated that the K + selective filter in AKT1 originated from streptophyte algae and is evolutionarily conserved in land plants. Silencing of HvAKT1 resulted in significantly decreased biomass and suppressed K + uptake in root epidermal cells under drought treatment. Disruption of HvAKT1 decreased root H + efflux, H + -ATPase activity, and nitric oxide (NO) synthesis, but increased hydrogen peroxide (H2 O2 ) production in the roots under drought stress. Furthermore, we observed that overexpression of HvAKT1 improves K + uptake and increases drought resistance in barley. Our results highlight the importance of HvAKT1 for root K + uptake and its pleiotropic effects on root H + -ATPase, and H2 O2 and NO in response to drought stress, providing new insights into the genetic basis of drought tolerance and K + nutrition in barley.